A reforma psiquiátrica e seus rebatimentos sobre as famílias atendidas nos CAPS I da 20ª Regional de Saúde do Paraná - Salvalagio, Ana Rosa (2018)
Currently, Mental Health care is the reflection of numerous discussions and changes that culminated in the Psychiatric Reform process, which aims to gradually replace Psychiatric Hospitals with community-based open services, such as the Psychosocial Care Center (PCC), considered one of the main provisions of Mental Health policy. The family institution was historically moved away from the person with mental disorder, but throughout the historical process and the changes in Mental Health Policy, this was taken as a partner in the care. In this context, the impacts generated by the need for family care for mental disorders are also related to the peculiarity of social policies in Brazil (generally, focalists, precarious and welfarist), and Mental Health, being one of these policies, does not escape its logic. As the PCC is a currently the strategic equipment of the Mental Health Policy, users and their families are key subjects to understand the problem to be researched, namely: To what extent the implementation of the Psychiatric Reform generates impacts on the families served in the PPC I of the 20th Regional of Health of Paraná? What are these impacts? Or, what kind of refuting were produced about the family in the face of the need to care for a member with mental disorder posed by the logic of family and community life in which the Psychiatric Reform is based? In order to respond to this research problem, this research proposal is carried out through the qualitative approach, through exploratory research. To do this, an empirical study is carried out by the research subjects: families of people with mental disorders treated in the PCC I of the municipalities of the 20th Regional Health Center of Paraná (cities of Assis Chateaubriand, Palotina, Guaíra, Marechal Cândido Rondon, and Santa Helena). The purpose of this study is to: seize, understand and analyze the refuting / impacts of the implementation of the Psychiatric Reform on the families served in the PCC I by the referred Health Region. The semi-structured interview is used as a methodology and the data are interpreted collected through the technique of content analysis. The results show that PCC I need to implement actions that address families as caregivers, but also need care. Despite insufficient family-directed activities, family members demonstrate satisfaction with the performance of PCC related to the treatment mental disorder patients. We conclude that the Psychiatric Reform as a process of tensions and contradictions, which permeate capitalist society itself, has its weaknesses; however, it is still a very important proposal for the construction of new forms of care and new relations between Family / User / Services. In spite of this importance, it is clear in the discourses of family members, the role of the family as a private agent of social protection, when assuming the functions of protection that the State should exercise, evidencing a family overloaded with the demands of care. It is hoped that this research allows important reflections for professionals and managers of Mental Health, once the approximation with the reality of the users of the PCC I and their relatives, relevant quantitative and qualitative data on the familiar coexistence was obtained, giving support for new interventions.